Materials of International Practical Internet Conference “Challenges of Science” 2022
DOI: 10.31643/2022.08
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Job Satisfaction on Service Quality mediated by Lecturer Performance at State Universities

Abstract: Job satisfaction achieved by lecturers can affect all aspects of productivity, from performance to the quality of services provided in the academic community. This study focuses on analyzing the effect of job satisfaction on service quality with the performance of lecturers as mediators. This study uses an explanatory research method involving 140 respondents from lecturers who teach at state universities. Respondents were chosen by the simple random technique to fill in the questionnaire instrument with the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…The significance of this is that English's prevalence in scholarly publishing, as noted by Crystal [24] and Graddol [25], makes it an important consideration. Moreover, some other studies have also indicated that English-language publications carry more weight in terms of academic promotion and research grant applications in universities worldwide [26,27,28]. Even though civil servants may encounter various obstacles related to language, structure, organization, and ideology that can affect their decision to explore local publishing options, publishing their work in English can help them attain global recognition.…”
Section: Resultsmentioning
confidence: 99%
“…The significance of this is that English's prevalence in scholarly publishing, as noted by Crystal [24] and Graddol [25], makes it an important consideration. Moreover, some other studies have also indicated that English-language publications carry more weight in terms of academic promotion and research grant applications in universities worldwide [26,27,28]. Even though civil servants may encounter various obstacles related to language, structure, organization, and ideology that can affect their decision to explore local publishing options, publishing their work in English can help them attain global recognition.…”
Section: Resultsmentioning
confidence: 99%
“…Szelągowska-Rudzka (2018) emphasized that universities' success depends on their human resources. In addition, lecturers' motivation, delivery ability, performance, and professionalism correlate with a significant and positive effect on the quality of academic services (Aprilia, 2012;Chairunnisa, 2016;Memah et al, 2021;Muh. Asriadi et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…By meeting employees' needs through internal marketing, service organisations create job satisfaction (Kahsay, 2016). Job satisfaction influences worker attitude, reduces absenteeism, creates customer-conscious employees whose primary emphasis is on creating service excellence, and reduces employee turnover (Asriadi et al, 2022). Internal marketing enables service firms to deliver customer services by coordinating, aligning and motivating staff (Petrovsky, Ge, and Jinhai, 2022).…”
Section: Problem Statementmentioning
confidence: 99%
“…Job satisfaction is considered an individual worker's assertiveness to the job content (Putri et al, 2022). Research has shown that job satisfaction positively influences service quality (Muh. Asriadi et al, 2022;Putri et al, 2022).…”
Section: Chitungwiza Central Hospitalmentioning
confidence: 99%
See 1 more Smart Citation